Carabid beetles (Coleoptera: Carabidae) in several types of forests on Hokkaido, Japan, with implications for forest management practices and beetle preservation - Jun KAIZUKA; Tamaki YAMAGUCHI; Mitsuhiro IWASA (European Journal of Entomology, 2020)
This study of the role the environment in the composition of the communities of carabid beetles was carried out in several types of forests at Obihiro and Furano, Hokkaido, Japan. In addition, we analysed the altitudinal distributions of two forest specialists, Damaster gehinii (Faimaire) and Procrustes kolbei Roeschke, which occur in six mountain forests on Hokkaido. At Obihiro, the forest specialist, P. kolbei was found at only one site in a large area of broadleaf forest. A redundancy analysis indicated that the carabid assemblages were significantly different in the different types of forest, and that two species, Leptocarabus arboreus arboreus (Lewis) and Leptocarabus opaculus opaculus (Putzeys), were associated with broadleaf forests. At Furano, a forest specialist D. gehinii and a forest generalist Cychrus morawitzi Gehin were mainly collected in natural broadleaf and mixed forests, whereas the percentage made up of L. o. opaculus was very high (80.8%) in natural broadleaf forest. Pterostichus thunbergii Morawitz made up the highest percentage of the species in the conifer plantations. In the six mountain forests, D. gehinii was scarce and mainly occurred at low altitudes; however, P. kolbei was relatively abundant and mainly recorded at middle to high altitudes. The management of the forests on Hokkaido needed to maintain the diversity and abundance of carabid beetles is discussed.